IMPROVING THE ECONOMIC EFFICIENCY OF BUSINESS ENTITIES - Egamberdiyev Shavkatbek; Nuriddinov Abdulaziz (Лучшие интеллектуальные исследования, 2024)
Annotation. This article provides information on the study of various methods to improve the economic efficiency of small businesses. Feedback has been provided on which methods are more effective to improve the effectiveness of entrepreneurial subjects, which methods are futile. What is currently being done in Uzbekistan to improve efficiency is described.